تحليل العلاقة و الأثر بين متطلبات إدارة الجودة الشاملة والاداء التشغيلي للمصارف : دراسة على مجموعة مختارة من المصارف الاهلية في مدينة الموصل - د. اكرم احمد الطويل; زهراء صالح حمدي (PROSPECTIVE RESEARCHES, 2023)
t This study aimed at analysing the relation and imprint of the total quality management requirements on bank operational performance (a stduy that included a chosen group of private banks in Mosul ).The total quality management requirements have an out standing role in bank operational performance buildup. And because of the limitedness of the studies that handl the relation and the influence between the requirements of the total quality management and performance especially in the Iraqi environment, the researchers intended to include this advanced study ,to the extents of advantages within a comprehensive frame in an attempt to study the relation and the influence among them. In general, this study tries to answer the following questions: 1-Have the workers in the researched banks, an obvious vision about the total quality management requirements? 2- Have the workers in the researched banks an obvious vision about the operational performance? 3- Have the worker in the researched banks an obvious vision about the relation and the influence between the requirements of the total quality management and operational performance? The study has concluded a set of conclusions, the most important of them are: -There is a significant Correlation relation between total quality management requirements and operational performance. -There is a significant effect of the total quality management requirements in operational performance for researched banks . Depending on the Conclusions of the study, a number of recommendations which agree with the Conclusions are produced.